Management Strategy of Village-Owned Enterprises in Increasing Village Original Income - Umiyati*, Sri; Wahyuni, Sri (Universitas Syiah Kuala, 2023)
Pesanggrahan Village is a village located in Batu District, Batu City which has a BUMDes (Village-Owned Enterprise), namely BUMDes Mayangsari. This BUMDes in Pesanggrahan Village is also regulated in Village Regulation No.1 of 2017 concerning Village-Owned Enterprises. The purpose of this research is to explain the management strategy of Village-Owned Enterprises in increasing the village's original income in Pesanggrahan Village, Batu District, Batu City. Data collection techniques in this study using observation, interviews, and documentation. The results of this study, from the theory of strategic management, two indicators are going well, namely the preparation of strategies and evaluation and control and there are two indicators that have not gone well, namely observing the environment and implementing strategies. namely, 1) For officials or daily administrators of BUMDes Mayangsari by holding discussions that discuss the structure, budget, and human resources as well as existing natural resources as a form of introspection of management. 2) BUMDes Mayangsari should add and collaborate with more efforts from the village's original community and communities in Pesanggrahan Village and Batu City. 3) BUMDes Mayangsari should conduct evaluations that are held every 3 months such as quarterly, to improve the quality and quantity of BUMDes Mayangsari.